LANDFORMS AND GEOMORPHOSITES ONGOING CHANGES: CONCEPTS AND IMPLICATIONS FOR GEOHERITAGE PROMOTION - Pelfini, Manuela; Bollati, Irene (Quaestiones Geographicae, 2014)
The promotion of geological and geomorphological heritage is growing in importance for educational initiatives. The constantly increasing interest towards changing landforms due to changing climate conditions asks not only for improving the values of the cultural proposals but also for précising the subject of the discussion. Cultural trails and natural resources valorisation are more and more frequently based on the concept of geomorphosite, which is strictly linked to landform typology definitions. In sensitive areas, changing geomorphosites are considered of great interest as a typical response to changes in climate. In this paper, on the basis of recent research, we discuss the definitions of landforms and geomorphosites activity in relation to surface processes dynamics. In addition, we discuss the implications of geomorphological surface processes for geomorphosite evolution and degradation and their consequent impact on related valorisation activities. We indicate how both active and passive landforms, and therefore geomorphosites, are of great interest for scientific, educational and tourism purposes.